Preserving the Karia tradition: Symbolic meaning and social role in contemporary Muna community - Nur Amelia Devi; Rhoma Dwi Aria Yuliantri; Mhd Asrian Syah (Universitas Muhammadiyah Malang, 2025)
This study explores the symbolic meanings and social roles of the Karia tradition in Muna society, highlighting its contribution to preserving cultural identity in the face of modernisation. Employing a descriptive qualitative approach, data were gathered through participant observation, in-depth interviews, and documentation involving eight informants from diverse social backgrounds. Through this approach, the research seeks to understand how the Karia tradition continues to serve as a bridge between ancestral heritage and contemporary life, ensuring that cultural values remain alive and relevant across generations. The analysis was carried out using thematic analysis and Victor Turner's theory of ritual passage. The research results show that the Karia tradition symbolises female maturity and a means of character education and self-purification. This ritual also strengthens social cohesion and teaches important values such as chastity and social responsibility. However, the forces of modernisation and digitalisation pose challenges to the continuity of this tradition, particularly among younger generations who are becoming increasingly detached from traditional practices. This study contributes to the field of cultural anthropology by deepening the understanding of rites of passage and their evolving relevance in modern society. It also offers insights and recommendations on how digitalisation can be used not as a threat, but as a tool to revitalise and preserve local cultural heritage ensuring that traditions like Karia continue to thrive in contemporary contexts. Penelitian ini mengeksplorasi makna simbolik dan peran sosial tradisi Karia dalam masyarakat Muna, dengan menyoroti kontribusinya dalam menjaga identitas budaya di tengah arus modernisasi. Dengan menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi yang melibatkan delapan informan dari berbagai latar sosial. Melalui pendekatan ini, penelitian berupaya memahami bagaimana tradisi Karia tetap berfungsi sebagai jembatan antara warisan leluhur dan kehidupan modern, memastikan bahwa nilai-nilai budaya tetap hidup dan relevan lintas generasi. Analisis data dilakukan menggunakan analisis tematik dengan landasan teori Victor Turner tentang ritus peralihan. Hasil penelitian menunjukkan bahwa tradisi Karia melambangkan kedewasaan perempuan serta menjadi sarana pendidikan karakter dan penyucian diri. Ritual ini juga memperkuat kohesi sosial dan mengajarkan nilai-nilai penting seperti kesucian serta tanggung jawab sosial. Namun, arus modernisasi dan digitalisasi menghadirkan tantangan bagi keberlanjutan tradisi ini, terutama di kalangan generasi muda yang semakin terlepas dari praktik tradisional. Penelitian ini memberikan kontribusi terhadap bidang antropologi budaya dengan memperdalam pemahaman tentang ritus peralihan dan relevansinya yang terus berkembang dalam masyarakat modern. Selain itu, penelitian ini menawarkan wawasan dan rekomendasi tentang bagaimana digitalisasi dapat dimanfaatkan bukan sebagai ancaman, tetapi sebagai alat untuk menghidupkan kembali dan melestarikan warisan budaya lokal, sehingga tradisi seperti Karia dapat terus bertahan dan berkembang dalam konteks kontemporer.